(untitled) (Quest Journal of Management and Social Sciences, 2021)
Background: Since 2019, the government of Zimbabwe has been making fiscal transfers to local governments as part of fulfilling the constitutional provisions to improve the socio-economic wellbeing of communities. Despite these transfers, there is limited research that establishes whether the funds are achieving the intended results. Objective: The main focus of this paper was to assess progress towards the enhancement of the socio-economic rights of communities in the Mashonaland Central province of Zimbabwe through fiscal decentralization. Method: This paper adopted qualitative methodology and the case study as the design. The Mashonaland Central province was purposively selected as it is one of the regions lagging in terms of development. Data was collected through, documentary analysis and key informant interviews with ten councilors, one Town clerk, nine Chief Executive Officers as well as ten focus group discussions with community members. Findings: The study noted that since the transfer of funds to local authorities started in 2019, significant progress has been achieved in the fulfillment of socio-economic rights. However, local governments were facing challenges such as the unavailability of an administrative manual to guide them in the implementation of fiscal decentralization, lack of clear funds allocation criteria, untimely and unpredictable distribution of funds, price instability, cumbersome procurement processes and lack of a monitoring and evaluation framework. These challenges were negatively affecting the attainment of the desired goals. Conclusions and Recommendations: Fiscal devolution has already started paying dividends in enhancing the socio-economic rights of communities in the Mashonaland Central Province of Zimbabwe in key sectors such as water and sanitation, education, healthcare, infrastructure development, governance and administration, and peace and security. There is a need to develop an administrative manual for implementing fiscal devolution, timely disbursement devolution funds, use of virtual meetings in the wake of the Covid- 19 pandemic, integration of monitoring and evaluation mechanisms, and capacity building of local government policymakers and administrators.